Background Note for Eighth Five Year Plan (1992-97) and Annual Plan (1992-93) of Department of Heavy Industry - Planning Commission, Government of India (Planning Commission, Government of India, 1992)
The 8th Plan proposals of the units under the Department of Heavy Industry, including the physical and financial performance of the individual units, were considered in a series of meetings taken by Adviser (I&M) with representatives of DHI and the concerned units. The projects costing above Rs 20 crores were discussed with the help of resource based networks in consultation with the Adviser (Monitoring). The main points emerging out of these discussions are discussed in the subsequent paragraphs.
Planning Commission (Industry and Minerals Division)
Planning Commission (Industry and Minerals Division)
Keywords: Eighth Five Year Plan-Industry and Minerals Division